Comparing the effectiveness of training course formats for point‐of‐care ultrasound in the third trimester of pregnancy. Issue 1 (10th January 2019) - Westerway, Susan Campbell
Abstract: Introduction: The availability of obstetric point‐of‐care ultrasound (PoCUS) services has been shown to improve pregnancy outcomes in regional and remote areas both in Australia and around the world. There is an increasing demand for efficient, cost‐effective PoCUS courses for monitoring the fetus in the third trimester of pregnancy. Aim: To compare the effectiveness of targeted PoCUS courses provided for health professionals that assess the fetus during the third trimester of pregnancy. Method: The skill‐teaching curriculum and competency outcomes of six obstetric PoCUS courses were compared. There were 55 learners with no prior ultrasound experience including 23 with English as a second language. Course duration ranged from 4 to 18 h, didactic lecture time up to 6 h and practical scanning sessions of 3–12 h. Learner/tutor ratio varied from 1:1 to 6:1. All courses included the teaching of knobology, image optimisation and probe manipulation. Practical sessions included supervised scanning of ultrasound phantoms and scanning women in the third trimester of pregnancy. The teaching outcomes that were assessed included image optimisation, determination of fetal lie, fetal heart rate, measuring the single deepest pocket of amniotic fluid, identifying the placental position and basic fetal biometry. The same pre‐ and post‐course multiple choice test and course evaluation forms were used for every programme. Results: All participants achieved the limited course objectives, regardless of the differences in the course formats. Conclusion: This study confirms that obstetric PoCUS courses can provide the initial basic knowledge and scanning skills required to perform limited scope third‐trimester scanning.